A method for degrading antibiotics in water by activating persulfate with bimetallic hydroxycarbonate
By using the bimetallic carbonate hydroxy salt FexCo2-x(OH)2CO3 catalyst to activate PMS, the problem of difficult cycle conversion of Co(II)/Co(III) in the Co(II)/PMS system was solved, and the effect of efficient degradation of antibiotics in water was achieved, and the catalyst had good recycling properties.
Patent Information
- Application Number
- CN202410283761.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-03-13
AI Technical Summary
During the degradation of antibiotics in water, the existing Co(II)/PMS system has problems such as Co(II)/Co(III) difficult to cycle and conversion, difficult catalyst recovery, and removal efficiency needs to be improved.
The bimetallic hydroxycarbonate salt FexCo2-x(OH)2CO3 is used as a catalyst to increase the active site through the introduction of iron, activate PMS, and promote the reduction of Co(III) to Co(II) through Fe(II), realize the Co(II)/Co(III) cycle transformation, and generate highly active species for antibiotic degradation.
The cyclic conversion of Co(II)/Co(III) is achieved, the continuous activation effect of PMS is improved, and the degradation efficiency of antibiotics in water is significantly improved, especially the removal rate of sulfamethacil reaches 100%, and the catalyst can be recycled.
Smart Images

Figure CN118405774B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water pollution treatment, and specifically relates to a method for utilizing bimetallic hydroxycarbonate salt to activate hydrogen persulfate to degrade antibiotics in water. Background Art
[0002] In the past century, antibiotics have been widely used to prevent and treat bacterial infections and have promoted the development of animal husbandry and aquaculture. Unfortunately, antibiotics have unique characteristics such as a wide variety, high toxicity, long half-life, strong mobility, and stable structure, which pose a serious threat to the safety of aquatic ecosystems and human health. Sulfadimethoxine (SDM) is a typical heterocyclic sulfonamide antibiotic, which is widely used in medicine and veterinary medicine as an antibacterial agent. Due to its large usage and wide range of use, it has been frequently reported to be detected in water bodies, soil, and crops. In my country's surface water, urban sewage, pig wastewater and other water bodies, SDM is frequently detected at the ng / L or even μg / L level, posing a potential hazard to people's health.
[0003] Persulfate (PMS) advanced oxidation technology has attracted widespread attention due to its high efficiency in degrading antibiotics. Persulfate can generate highly oxidizing sulfate radicals after being activated by light, heat, ultrasound, and transition metals. Among the many ways to activate PMS, transition metal ions have attracted widespread attention due to their low cost and simple operation. Cobalt ions (Co(II)) are widely used in persulfate activation systems and have a good effect on the removal of difficult-to-degrade organic matter in water. However, the Co(II) / PMS system has obvious limitations: (1) The large amount of metal ion residues in water is harmful to the ecological environment; (2) Excessive metal ion concentration can easily lead to free radical scavenging effects, thereby weakening the treatment effect; (3) Co(II) / Co(III) is difficult to recycle and transform; (4) The pH conditions of the solution have a great impact on the catalytic effect.
[0004] However, the current use of divalent cobalt to activate persulfate systems has problems such as Co(II) / Co(III) being difficult to circulate and cannot be recycled and reused, and the removal efficiency needs to be improved. Therefore, the art needs to seek suitable materials to promote the cyclic conversion of Co(II) / Co(III), achieve continuous activation of PMS, and achieve better activation effects. The present invention provides a method for degrading antibiotics in water by activating bisulfate using bimetallic carbonate. The technical principle is as follows: the present invention is a cobalt hydroxycarbonate iron (Fe x Co 2-xThe introduction of iron into the composite material increases the active sites of cobalt carbonate (Co2(OH)2CO3), which can better activate PMS. At the same time, the introduction of iron can promote the cobalt-iron double cycle. Fe(II) can also reduce Co(III) to Co(II), promoting the Co(II) / Co(III) cycle. During the reaction, the amount of Co(II) increases, and the electron transfer of Co(II) to hydrogen persulfate is enhanced, which stimulates the production of strong oxidizing HO - 、SO4 - and 1 O2 and high-valent metals, thereby further efficiently degrading antibiotics in water, especially sulfonamide antibiotic sulfadimethoxine. The reaction process involved is as follows:
[0005] Co 2+ +HSO5 — →Co 3+ +HO·+SO4 2- (1)
[0006] Co 2+ +HSO5 — →Co 3+ +OH - +SO4 ·- (2)
[0007] Co 3+ +HSO5 — →Co 2+ +H + +SO5 ·- (3)
[0008] Fe 2+ +Co 3+ →Co 2+ +Fe 3+ (4)
[0009] Fe 2+ +HSO5 — →Fe 3+ +SO4 2- +HO·(5)
[0010] Fe 2+ +HSO5 — →Fe 3+ +OH - +SO4 ·- (6)
[0011] Fe 3+ +HSO5 — →Fe 2+ +H + +SO5 ·- (7)
[0012] Co 2+ +HSO5 — →Co(IV)+H + +SO4 2- (8)
[0013] Fe 2+ +HSO5 — →Fe(IV)+H + +SO4 2- (9). Summary of the invention
[0014] The present invention provides a method for utilizing bimetallic carbonate hydroxy salt to activate hydrogen persulfate to degrade antibiotics in water. x Co 2-x The (OH)2CO3 / PMS system produces highly active species (High-value metals and 1 O2) degradation of antibiotics in water solves the problem of difficult recycling and conversion of Co(II) / Co(III) and difficult recovery of catalysts in the Co(II) / PMS system, which pollutes the environment. The system has a small amount of material addition, fast degradation speed and high efficiency.
[0015] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: a method for degrading antibiotics in water by activating hydrogen persulfate with bimetallic carbonate hydroxy salt, using bimetallic carbonate hydroxy salt Fe x Co 2-x (OH)2CO3 is used as a catalyst to activate persulfate to degrade antibiotics in water. The specific steps are as follows: bimetallic hydroxycarbonate and persulfate are added to the water in sequence and stirred to form a degradation reaction system to complete the degradation of antibiotics in the water; wherein the antibiotics are sulfonamide antibiotics.
[0016] Furthermore, the Fe x Co 2-x The time interval for adding (OH)2CO3 and hydrogen persulfate into the water body is 1 min-5 min; the stirring speed is 100 r / min-500 r / min; the degradation time of the degradation reaction system is 20 min-120 min, preferably 30 min-60 min, the degradation temperature is 15°C-35°C, preferably 15°C-30°C, and the initial pH value of the degradation reaction system is 3-11, preferably 3-9.
[0017] Furthermore, the content of the antibiotic in the water is ≤15 mg / L, preferably ≤5 mg / L.
[0018] Furthermore, the Fe x Co 2-xThe specific preparation steps of (OH)2CO3 are as follows:
[0019] (1) dispersing ferric nitrate nonahydrate Fe(NO3)3·9H2O, cobalt nitrate hexahydrate Co(NO3)2·6H2O and urea CH4N2O into an ultrapure aqueous solution to form a dispersion, stirring the dispersion evenly, placing the dispersion in an autoclave for hydrothermal reaction at 160°C-190°C for 3h-5h, and then cooling and collecting the precipitate;
[0020] (2) washing the precipitate obtained in step (1) three times and then centrifuging to collect the precipitate at the bottom of the centrifuge tube;
[0021] (3) The precipitate obtained in step (2) is transferred to an oven for drying to obtain a magnetic bimetallic hydroxy carbonate Fe x Co 2-x (OH)2CO3, store in a sealed bag for later use.
[0022] Furthermore, in the step (1), the concentration of ferric nitrate nonahydrate in the dispersion is 2.5 g / L-3.0 g / L, the concentration of cobalt nitrate hexahydrate is 10.0 g / L-15.0 g / L, the concentration of urea is 42.5 g / L-43.0 g / L, and the stirring time is 20 min-40 min; the liquid used for washing in the step (2) is water, ethanol or ethanol aqueous solution; and the drying temperature in the step (3) is 60° C.-80° C., and the drying time is 20 h-24 h.
[0023] Furthermore, the Fe x Co 2-x Morphology of (OH)2CO3 The broken Co2(OH)2CO3 nanosheets grew into irregular morphology of grape-like microspheres, in which cobalt accounted for 50%-70%, iron accounted for 2%-10%, carbon accounted for 5%-20%, and oxygen accounted for 20%-40%.
[0024] Furthermore, the hydrogen persulfate is any one of potassium hydrogen persulfate, sodium hydrogen persulfate, a potassium hydrogen persulfate composite salt or a sodium hydrogen persulfate composite salt.
[0025] Furthermore, the sulfonamide antibiotic is sulfadimethoxine.
[0026] Furthermore, in the degradation reaction system, the initial content of hydroxy carbonate is 10 mg / L-50 mg / L, preferably 20 mg / L-40 mg / L; - The initial concentration of hydrogen persulfate is 0.25 mmol / L-4.0 mmol / L, preferably 0.5 mmol / L-2.0 mmol / L.
[0027] The beneficial effects that can be achieved by at least one of the above technical solutions adopted in the embodiments of the specification include at least:
[0028] (1) The magnetic bimetallic hydroxy carbonate Fe prepared by the present invention x Co 2-x The (OH)2CO3 composite material is synthesized by modifying Co2(OH)2CO3 with Fe(NO3)3 9H2O. It not only uses the introduction of ferric nitrate nonahydrate to dope Fe into cobalt carbonate hydroxyl, giving the catalyst material magnetism, but also increases the specific surface area of the catalyst, which is conducive to increasing more active sites, ensuring the excellent performance of the catalyst and stable and controllable preparation.
[0029] (2) The present invention uses Fe for the first time x Co 2-x The (OH)2CO3 / PMS system produces highly active species (High-value metals and 1 O2) degradation of antibiotics in water, solving the problem of difficult recycling of Co(II) / Co(III) and difficult recovery of catalysts in the Co(II) / PMS system, which pollutes the environment. The system has a small amount of material addition, fast degradation speed and high efficiency. It can completely remove 5 mg / L sulfadimethoxine in water within 30 minutes.
[0030] (3) Fe of the present invention x Co 2-x( The OH)2CO3 / PMS system further expands the applicable pH environment, and has a good degradation effect at pH 3-11, especially at pH 3-9, with a high removal rate, which solves the problem that Co(II) / PMS is difficult to apply in practice due to pH restrictions;
[0031] (4) Fe of the present invention x Co 2-x (OH)2CO3 / PMS system has some common anions (HCO3 - and Cl - ) can still remove sulfadimethoxine, and the removal rate can still reach 100%; in addition, Fe x Co 2-x The (OH)2CO3 / PMS system has good stability. The degradation effect of the catalyst is basically unchanged before and after the degradation reaction. After the degradation reaction is completed, the Fe x Co 2-x (OH)2CO3 separation, recovery, cleaning, drying, and reuse can achieve almost complete degradation of sulfadimethoxine within 30 minutes after three cycles;
[0032] (5) The application method of the present invention is simple, does not require complex equipment, has mild reaction conditions, can be rapidly degraded at room temperature and pressure, has strong operability, and has broad practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0034] Figure 1 Fe prepared in Example 1 x Co 2-x Scanning electron microscope SEM image of (OH)2CO3, where (A) is Fe x Co 2-x (OH)2CO3 morphology, (B) Fe x Co 2-x Detailed zoomed image of (OH)2CO3;
[0035] Figure 2 Fe x Co 2-x Analysis of the proportions of cobalt, iron, carbon and oxygen elements in (OH)2CO3.
[0036] Figure 3 Fe prepared in Example 1 x Co 2-x X-ray diffraction (XRD) diagram of (OH)2CO3 / PMS, where the horizontal axis is 2θ (°) and the vertical axis is intensity (au); the XRD patterns from top to bottom represent the Fe x Co 2-x (OH)2CO3, Fe after degradation reaction x Co 2-x (OH)2CO3;
[0037] Figure 4 It is the degradation efficiency diagram of Example 2;
[0038] Figure 5 It is the degradation efficiency diagram of Example 3;
[0039] Figure 6 It is the degradation efficiency diagram of Example 4;
[0040] Figure 7 For the different concentrations of HCO3 in Example 5 - Fe x Co 2-xDegradation efficiency diagram of the effect of (OH)2CO3 / PMS on the degradation efficiency of sulfadimethoxine;
[0041] Figure 8 The different concentrations of HA in Example 5 are x Co 2-x Degradation efficiency diagram of the effect of (OH)2CO3 / PMS on the degradation efficiency of sulfadimethoxine;
[0042] Fig. 9 For different concentrations of Cl in Example 5 - Fe x Co 2-x Degradation efficiency diagram of the effect of (OH)2CO3 / PMS on the degradation efficiency of sulfadimethoxine;
[0043] Fig.10 This is the degradation efficiency diagram of Example 6. DETAILED DESCRIPTION
[0044] The embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0045] The following describes the implementation methods of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that, in the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.
[0046] The terms involved in the present invention are:
[0047] In the present invention, "Co(II)" or "cobalt ion" both refer to divalent cobalt ions.
[0048] In the present invention, "water" refers to ultrapure water, and "room temperature" refers to 15-30°C.
[0049] Example 1Fe x Co 2-x Preparation of (OH)2CO3
[0050] (1) 0.2020 g of ferric nitrate nonahydrate Fe(NO3)3·9H2O, 0.7276 g of cobalt nitrate hexahydrate Co(NO3)2·6H2O and 3 g of urea CH4N2O were dispersed in 70 mL of ultrapure water and stirred for 30 min to form a dispersion. After stirring evenly, the dispersion was placed in a stainless steel autoclave (100 mL) with a Teflon lining and subjected to hydrothermal reaction at 180°C for 3 h, then cooled and the precipitate was collected;
[0051] (2) washing the precipitate obtained in step (1) with ultrapure water and ethanol three times respectively, and then centrifuging to collect the precipitate at the bottom of the centrifuge tube;
[0052] (3) The precipitate obtained in step (2) was transferred to an oven at 80° C. and dried for 24 h to obtain a magnetic bimetallic hydroxycarbonate Fe x Co 2-x (OH)2CO3, store in a sealed bag for later use.
[0053] The Fe prepared in Example 1 x Co 2-x (OH)2CO3 was observed by scanning electron microscope (German ZEISS GeminiSEM300). The specific method was to take a small amount of sample and stick it directly on the conductive glue, and use Quorum SC7620 sputtering coater to spray gold for 45s, and the gold spraying current was 10mA; then use ZEISS GeminiSEM 300 scanning electron microscope to take pictures of sample morphology, energy spectrum mapping and other tests. The acceleration voltage was 3kV when taking morphology pictures, and 15kV when taking energy spectrum mapping pictures. The detector was SE2 secondary electron detector. The results are shown in Figure 1 As shown, Figure 1 Display: Cobalt iron carbonate (Fe x Co 2-x The morphology of (OH)2CO3) is an irregular morphology of grape-like microspheres grown on broken Co2(OH)2CO3 nanosheets. Figure 2 It shows that the Fe prepared by the present invention x Co 2-x In (OH)2CO3, cobalt accounts for 50-70%, iron accounts for 2-10%, carbon accounts for 5-20%, and oxygen accounts for 20-40%. Such an irregular structure adds more active sites, ensuring the excellent performance of the catalyst, and also shows that the preparation method is stable and reliable.
[0054] The Fe prepared in Example 1 x Co 2-x (OH)2CO3 was tested by X-ray diffraction (Shimadzu XRD-6100, Japan), and the results are as follows Figure 3Comparison of the XRD patterns before and after the degradation reaction shows that the patterns, peak positions, and peak heights before and after the degradation reaction are similar, indicating that Fe x Co 2-x (OH)2CO3 does not undergo obvious structural changes and has structural stability.
[0055] Example 2 Effect of Persulfate (PMS) Dosage on Fe x Co 2-x Effect of (OH)2CO3 / PMS on the degradation efficiency of sulfadimethoxine
[0056] Take five groups of sulfadimethoxine aqueous solutions with an initial concentration of 5.0 mg / L, 200 mL each, to simulate the antibiotic wastewater system, and add 10 mg / L Fe x Co 2-x (OH)2CO3 catalyst, adjust the system pH to 6.0, then add 0mmol / L, 0.25mmol / L, 0.5mmol / L, 1.0mmol / L and 2.0mmol / L potassium persulfate complex salt, and stir at room temperature for 30min to perform degradation reaction. Samples were taken during the degradation reaction: 0.8mL of solution was taken out at 0min, 2min, 4min, 6min, 8min, 10min, 15min, 20min, and 30min, respectively, and added to a centrifuge tube containing 0.2mL of sodium thiosulfate, shaken evenly to terminate the degradation reaction, and filtered through a 0.22μm filter membrane and stored in a 2mL liquid phase vial for the determination of sulfadimethoxine concentration.
[0057] Determination of removal rate: Place the liquid vial containing the sulfadimethoxine sample solution into the high performance liquid chromatograph for testing. Figure 4 As shown, the removal rate calculation formula is as follows:
[0058]
[0059] Where: C t represents the real-time concentration of pollutants, and C0 represents the initial concentration of pollutants.
[0060] Figure 4 The results showed that when the initial concentration of sulfadimethoxine was 5.0 mg / L and the system pH was 6.0, the addition of Fe x Co 2-x(OH)2CO3 has no obvious effect on the degradation of sulfadimethoxine within 30 minutes, and the removal rate is only 13%. The removal rates of sulfadimethoxine corresponding to 30 minutes of sulfadimethoxine are all 100% when the PMS dosage is 0.5mmol / L, 1.0mmol / L and 2.0mmol / L. Since PMS is the main source of active species in the catalytic system and the key factor in the catalytic degradation of sulfadimethoxine, the higher the PMS concentration, the more active species are produced. When the PMS concentration is increased to 0.5mmol / L and 1.0mmol / L, the degradation rate of sulfadimethoxine does not increase significantly because PMS has self-quenching performance. However, when the PMS concentration is 2.0mmol / L, the removal rate is further accelerated. This may be because the active species produced by the high enough PMS concentration can offset the self-quenching effect, so it does not inhibit the degradation of sulfadimethoxine but promotes it.
[0061] Example 3Fe x Co 2-x Effect of (OH)2CO3 dosage on Fe x Co 2-x Effect of (OH)2CO3 / PMS on the degradation efficiency of sulfadimethoxine
[0062] Take five groups of sulfadimethoxine aqueous solutions with an initial concentration of 5.0 mg / L, 200 mL each, to simulate the antibiotic wastewater system, and add 0 mg / L, 5 mg / L, 10 mg / L, 20 mg / L and 30 mg / L respectively to each group. x Co 2-x (OH)2CO3 catalyst, the pH value of the system was adjusted to 6.0, and then 0.5mmol / L potassium persulfate composite salt was added to each group, and then stirred at room temperature for 30min to perform degradation reaction. Samples were taken during the degradation reaction and the removal rate was determined. The specific operation was the same as in Example 2. The results are shown in FIG. Figure 5 shown.
[0063] Figure 5 The results showed that when the initial concentration of sulfadimethoxine was 5.0 mg / L and the system pH was 6.0, Fe x Co 2-x In (OH)2CO3 / PMS, the degradation effect of PMS alone on sulfadimethoxine was also not obvious within 30 minutes, with a removal rate of only 3.6%. x Co 2-xThe degradation rate of sulfadimethoxine increased with the increase of (OH)2CO3, because the introduction of more catalysts can increase the number of catalytic sites and activate more PMS to produce active species. However, when the amount of catalyst increased to 20mg / L to 60mg / L, the degradation rate of sulfadimethoxine did not increase significantly. Therefore, considering the cost of industrial water treatment, 10mg / L-20mg / L Fe x Co 2-x (OH)2CO3 is preferred.
[0064] Example 4Fe x Co 2-x Effect of (OH)2CO3 usage on Fe x Co 2-x Effect of (OH)2CO3 / PMS on the degradation efficiency of sulfadimethoxine
[0065] Take 200 mL of sulfadimethoxine aqueous solution with an initial concentration of 5 mg / L to simulate the antibiotic wastewater system, and add 10 mg / L of Fe x Co 2-x (OH)2CO3, adjust the pH value of each group to 6.0, and then add 0.5mmol / L of sodium persulfate composite salt. Stir at room temperature for 30 minutes to carry out degradation reaction. Take samples during the degradation reaction and measure the removal rate. Subsequently, the suspension after the degradation reaction is filtered with a filter membrane, washed with ultrapure water 3 times, and dried in a drying oven at 80°C for 24 hours to obtain a catalyst sample after one reaction. Repeat the above process with the sample after one reaction to obtain a catalyst sample after two reactions, and perform degradation experiments with the same operation. The specific steps of the degradation experiment are the same as those in Example 2. The results are as shown in the figure. Figure 6 shown.
[0066] Figure 6 The results showed that when the initial concentration of sulfadimethoxine was 5.0 mg / L and the system pH was 6.0, the addition of 10 mg / L Fe x Co 2-x In the case of (OH)2CO3 and 0.5mmol / L sodium persulfate complex salt, after three cycles of use, the degradation rate of sulfadimethoxine can still reach 97.5%, indicating that the synthesized Fe x Co 2-x (OH)2CO3 has good catalytic stability.
[0067] Example 5 Effect of different anions on Fe x Co 2-x Effect of (OH)2CO3 / PMS on the degradation efficiency of sulfadimethoxine
[0068] Take five groups of sulfadimethoxine aqueous solutions with an initial concentration of 5 mg / L, 200 mL each, simulate the antibiotic wastewater system, and add 10 mg / L Fe x Co 2-x (OH)2CO3, adjust the pH value of each group to 6.0, and then add Cl with concentrations of 0mmol / L, 1mmol / L, 2mmol / L, 5mmol / L and 8mmol / L respectively - Then add 0.5mmol / L sodium persulfate composite salt and stir at room temperature for 30min to carry out degradation reaction. The same operation is performed to add different concentrations of HCO3 - The degradation reaction was carried out with HA, and the samples were taken and the removal rate was determined. The operation was the same as in Example 2. The results are shown in FIG. Figure 7 , Figure 8 and Fig. 9 shown.
[0069] Figure 7 , Figure 8 and Fig. 9 The results showed that when the initial concentration of sulfadimethoxine was 5.0 mg / L and the system pH was 6.0, Fe x Co 2-x (OH)2CO3 / PMS with Cl - 、HCO3 - With the increase of HA dosage, the degradation rate of Sulfamethoxazole slowed down, but the degradation rate of Sulfamethoxazole in 10 minutes could still reach 73%, 99.0% and 98%. This is because the addition of anions and natural organic matter caused a part of highly oxidizing oxygen species to be transformed into low oxidizing oxygen species, but there were still a large number of active substances in the reaction system that could achieve efficient degradation of Sulfamethoxazole and had good resistance to external interference.
[0070] Example 6 Effect of different initial pH values on Fe x Co 2-x Effect of (OH)2CO3 / PMS on the degradation efficiency of sulfadimethoxine.
[0071] Take five groups of sulfadimethoxine aqueous solutions with an initial concentration of 5 mg / L, 200 mL each, to simulate the antibiotic wastewater system, and add 10 mg / L Fe x Co 2-x (OH)2CO3, respectively adjust the pH value of the system to 3, 6, 7, 9, 11, then add 0.5mmol / L sodium persulfate composite salt, stir at room temperature for 30min to carry out degradation reaction, take samples during the degradation reaction and measure the removal rate, the operation is the same as Example 2, the results are as follows Fig.10 shown.
[0072] Fig.10 The results showed that when the initial concentration of sulfadimethoxine was 5.0 mg / L, the application of Fe x Co 2-x The (OH)2CO3 / PMS system, the initial pH values were 3.0, 6.0, 7.0, 9.0, 11.0, and the corresponding 30-min removal rate of sulfadimethoxine all reached 100%. When the initial pH decreased from 6.0 to 3.0, the reaction rate constant k increased from 0.755min to 1.0. -1 Down to 0.635min -1 When the pH value was raised to 11.0, the reaction rate constant further decreased to 0.297 min -1 But in general, Fe x Co 2-x The degradation of sulfadimethoxine by the (OH)2CO3 / PMS system is not greatly affected by pH, especially when the pH range is 3.0-9.0, it can not only achieve a removal rate of 100%, but also has a good degradation rate.
[0073] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for degrading antibiotics in water by activating persulfate with bimetallic carbonate, characterized in that: Using double metal hydroxycarbonate Fe x Co 2-x (OH)2CO3 is used as a catalyst to activate hydrogen persulfate to degrade antibiotics in water. The specific steps are as follows: adding bimetallic carbonate hydroxy salt and hydrogen persulfate to the water in sequence and stirring to form a degradation reaction system to complete the degradation of antibiotics in the water; wherein the antibiotic is a sulfonamide antibiotic; The Fe x Co 2-x The specific preparation steps of (OH)2CO3 are as follows: (1) dispersing ferric nitrate nonahydrate Fe(NO3)3·9H2O, cobalt nitrate hexahydrate Co(NO3)2·6H2O and urea CH4N2O into an ultrapure aqueous solution to form a dispersion, stirring the dispersion evenly, placing the dispersion in an autoclave for hydrothermal reaction at 160°C-190°C for 3h-5h, and then cooling and collecting the precipitate; (2) washing the precipitate obtained in step (1) three times and then centrifuging to collect the precipitate at the bottom of the centrifuge tube; (3) The precipitate obtained in step (2) is transferred to an oven for drying to obtain a magnetic bimetallic hydroxy carbonate Fe x Co 2-x (OH)2CO3, stored in a sealed bag for future use; In the degradation reaction system, the initial content of hydroxy carbonate is 10mg / L-50mg / L; - The initial concentration of hydrogen persulfate is 0.25mmol / L-4.0mmol / L.
2. The method according to claim 1, characterized in that The Fe x Co 2-x The time interval for adding (OH)2CO3 and hydrogen persulfate into the water body is 1min-5min; the stirring speed is 100r / min-500r / min; the degradation time of the degradation reaction system is 20min-120min, the degradation temperature is 15℃-35℃, and the initial pH value of the degradation reaction system is 3-11.
3. The method according to claim 2, characterized in that The degradation time of the degradation reaction system is 30 min-60 min, the degradation temperature is 15° C.-30° C., and the initial pH value of the degradation reaction system is 3-9.
4. The method according to claim 1, characterized in that The content of the antibiotic in the water body is ≤15 mg / L.
5. The method according to claim 1, characterized in that The content of the antibiotic in the water body is ≤5 mg / L.
6. The method according to claim 1, characterized in that In the step (1), the concentration of ferric nitrate nonahydrate in the dispersion is 2.5 g / L-3.0 g / L, the concentration of cobalt nitrate hexahydrate is 10.0 g / L-15.0 g / L, the concentration of urea is 42.5 g / L-43.0 g / L, and the stirring time is 20 min-40 min; the liquid used for washing in the step (2) is water, ethanol or ethanol aqueous solution; the drying temperature in the step (3) is 60° C.-80° C., and the drying time is 20 h-24 h.
7. The method according to any one of claims 1 to 6, characterized in that: The Fe x Co 2-x The morphology of (OH)2CO3 is an irregular morphology of grape-like microspheres grown on broken Co2(OH)2CO3 nanosheets, in which cobalt accounts for 50%-70%, iron accounts for 2%-10%, carbon accounts for 5%-20%, and oxygen accounts for 20%-40%.
8. The method according to claim 1, characterized in that The persulfate is any one of potassium persulfate, sodium persulfate, a potassium persulfate composite salt or a sodium persulfate composite salt.
9. The method according to claim 1, characterized in that The sulfonamide antibiotic is sulfadimethoxine.
10. The method according to claim 1, characterized in that In the degradation reaction system, the initial content of hydroxy carbonate is 20mg / L-40mg / L; - The initial concentration of hydrogen persulfate is 0.5mmol / L-2.0mmol / L.
Citation Information
Patent Citations
Co2FeAl-LDH, preparation method of Co2FeAl-LDH and method for degrading pollutants
CN110801839A